Modeling the Availability of a Repairable Series Structure with two Units (2020)
When there is a structure with two serial components where each one owns a life time that is distributed exponentially and both of the components are repairable, it is established a renovation process, in which both components need to be working in order for the operation of the structure. It is observed that the renovation process evidences a semimarkovian behavior and it is shown that through this one, its availability function is one of the inquiries of a system of integral equations that is solved by a numerical method designed for that purpose. The novelty in this article is that it is considered a process whose state space includes repair time, which is useful in engineering applications.